Pengaruh Motivasi Belajar Dan Pemanfaatan Sumber Belajar Terhadap Hasil Belajar Siswa SMP Negeri 11 Pontianak - Farida, Ida (UNIVERSITAS TANJUNGPURA, 2014)
This study examines the effect of learning motivation and use of learning resources on learning outcomes IPS Junior High School eighth grade students 11 Pontianak. Indicators of motivation in this research include covering passion and Desire to learn, enthusiasm for learning, the need for learning, hope the outcomes of learning, and the ideals to be achieved, the indicator use of learning resources, including books and the internet. This study uses form of multiple linear regression. Source of data in this study is the respondents' answers to the questionnaire and student learning outcomes. Collecting data using questionnaires, interview and observation sheet. Results of the study are: (1) there is the influence of learning motivation on student learning outcomes was 23,5% as evidenced by tcount> ttable, is 6,015> 1.980; (2) a significant difference between the use of learning resources on student learning outcomes was 76,5% as evidenced by tcount > ttable, is 16,537> 1,980; (3) there is a significant relationship between motivation and use of learning resources to students' learning outcomes IPS was 74,9% as evidenced by Fvalue > F table, is 119,135> 3.072.Keywords: Learning Motivation, Learning Resources, Learning Outcomes.